Corticosteroids for reducing tuberculosis mortality in persons living with HIV: a systematic review and meta-analysis using reconstructed individual patient data - Sidibe Sidikiba; Oumou Hawa Diallo; Alhassane Diallo; Boubacar Djelo Diallo; Miguel Carlos-Bolumbu; Mohamed Camara (BMJ Global Health)
Objective To assess the effect of adjunctive corticosteroids on mortality in persons living with HIV (PLHIV) being treated for tuberculosis (TB).Design Systematic review and meta-analysis.Data sources PubMed, CENTRAL and EMBASE through 31 December 2023Study selection Randomised placebo-controlled trials (RCTs) with published Kaplan-Meier survival curves comparing corticosteroids versus placebo in PLHIV receiving TB treatment.Quality assessment, data extraction and analysis Three reviewers independently assessed study quality and extracted data. Reconstructed individual patient data were derived from published Kaplan-Meier survival curves, and a one-stage mixed-effects Cox regression model was used to estimate HRs for all-cause mortality.Results Four trials involving 873 PLHIV with three forms of TB (618 meningitis, 197 pleural and 58 pericarditis) were included. Over a median follow-up of 19.3 months (IQR, 15.1–30.2), 367 (42%) participants died. At 12 months after randomisation, corticosteroids were associated with a 67% reduction in mortality (HR 0.33, 95% CI 0.26 to 0.41; p<0.0001) compared with placebo. This benefit was maintained during the full follow-up period, with a 17% reduction in mortality (0.83, 0.68–0.99; p=0.0477). In subgroup analyses, a non-significant trend towards benefit was seen for TB meningitis (HR 0.84, 0.67–1.05; p=0.061, two trials), with unclear effect for pleural (HR 0.90, 0.57–1.41; p=0.643, one trial) and TB pericarditis (HR 0.40, 0.15–1.17; p=0.100, one trial).Conclusion Adjunctive corticosteroids were associated with reduced mortality among PLHIV treated for TB in this meta-analysis of four RCTs. Further clinical trials are needed to confirm this finding and inform guidelines on the use of adjunctive corticosteroid in this population.PROSPERO registration number CRD42024500865.